(untitled) (Altre Modernità, 2024)
Francesco Benozzo, The Ridge and the Song. Sailing the Archipelago of Poetry Preface by Antonella Riem Natale (Udine, Forum, 2022, 32 pp. ISBN 978-8832833416) by Saverio Tomaiuolo